Utilizing Whatsapp As A Medium Of Learning Activities Biology In The Pandemic Covid-19 - Nurlaily Chalizah. J; Teba Wati; Ade Irwansyah (CV. AFDIFAL MAJU BERKAH, 2021)
This study aims to describe the: (1) the Utilization of WhatsApp as a learning medium in the tissues of the pandemic of Covid-19 in class XI IPA SMA Negeri 1 Kecamatan Na.IX-X Kabupaten Labuhanbatu Utara (2) Obstacles that occur in the use of WhatsApp as a learning medium in the tissues of the pandemic of Covid-19 in class XI IPA SMA Negeri 1 Kecamatan Na.IX-X Kabupaten Labuhanbatu Utara (3) the Solution is to overcome the barriers in the use of WhatsApp as a learning medium in the tissues of the pandemic of Covid-19 in class XI IPA SMA Negeri 1 Kecamatan Na.IX-X Kabupaten Labuhanbatu Utara. This research was conducted in SMA Negeri 1 Kecamatan Na.IX-X North Labuhanbatu District in the July to September 2021. This type of research is qualitative descriptive type of research phenomenology that describes about the use of WhatsApp as a learning medium in the tissues of the pandemic Covid-19. Data from this study were obtained through an interview with the Guardian class which became the main source of this research, then interviews with 5 students of class XI IPA-A, observation form observation passive participation and documentation as supporting data from the results of the interview. The results of the research showed that the teachers have been utilizing WhatsApp as a learning media to support the learning activities in the network (Online) by utilizing the various features available such as features photos, videos, documents and video call. Then in the implementation of the utilization of WhatsApp as a medium of learning there are several obstacles, namely the interference Signal, the memory of the Mobile phone is full, the Lack of Interaction, it is difficult to know the seriousness of the learners, the lack of learning motivation of learners, supporting facilities for online learning, and it is difficult to understand the material given, as well as in this study decrypt the solution is to overcome the obstacles that occur from the use of whatsApp as a learning medium in the tissues of the pandemic Covid-19. From the results of this study it is suggested that educators are able to make learning variations, especially using the features of yag there on whatsApp, master and use of ICT in the learning process in the network (Online)